Students' Perception Of Blended Learning Method Implementing At English Education Department Of STAI Hubbulwathan Duri - Fitriana; Deswarni , Dini (Unit Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Agama Islam Hubbulwathan, Duri, Indonesia, 2023)
This research aims to find out the Students' Perception of Implementing Blended Learning Method at English Education Department of STAI Hubbulwathan Duri. This research is quantitative approach with a descriptive design. Descriptive research design is research that provides an overview of the object under study through a sample or population data as it is. In this study, researchers collected data using questionnaires. Data were obtained from 35 students of the English Education Department of STAI Hubbulwathan Duri. To find out the students’ perception, the scores gained from the closed-ended questionnaire were transformed into percentages to be analyzed. The result of this research showed that the students gave their positive perception toward the implementation of the Blended Learning Method in English Language Teaching. The positive judgment from the respondents came from their experience in learning by using Blended Learning Method. They enjoyed the learning process when the lecturer implemented Blended Learning Method. This research also reveals that Blended Learning Method was very beneficial for them. Blended Learning Method made them more interested in learning. In addition, become more active and responsible